The outward shaker channel OsK5.2 improves plant salt tolerance by contributing to control of both leaf transpiration and K+ secretion into xylem sap. (28th March 2022) - Zhou, Jing; Nguyen, Thanh‐Hao; Hmidi, Dorsaf; Luu, Doan‐Trung; Sentenac, Hervé; Véry, Anne‐Aliénor
Abstract: Soil salinity constitutes a major environmental constraint to crop production worldwide. Leaf K + /Na + homoeostasis, which involves regulation of transpiration, and thus of the xylem sap flow, and control of the ionic composition of the ascending sap, is a key determinant of plant salt tolerance. Here, we show, using a reverse genetics approach, that the outwardly rectifying K + ‐selective channel OsK5.2, which is involved in both K + release from guard cells for stomatal closure in leaves and K + secretion into the xylem sap in roots, is a strong determinant of rice salt tolerance (plant biomass production and shoot phenotype under saline constraint). OsK5.2 expression was upregulated in shoots from the onset of the saline treatment, and OsK5.2 activity in guard cells led to a fast decrease in transpirational water flow and, therefore, reduced Na + translocation to shoots. In roots, upon saline treatment, OsK5.2 activity in xylem sap K + loading was maintained, and even transiently increased, outperforming the negative effect on K + translocation to shoots resulting from the reduction in xylem sap flow. Thus, the overall activity of OsK5.2 in shoots and roots, which both reduces Na + translocation to shoots and benefits shoot K + nutrition, strongly contributes to leaf K + /Na + homoeostasis. Summary Statement: A reverse genetics approach shows that the dual activity of the outward shaker K + channel OsK5.2 in the root vasculature and in stomata strongly favours translocation to shoots of K + over Na + and thereby is highly beneficial for rice plant tolerance to salt stress. This gene provides a new possible target for plant breeders towards the improvement of tolerance to this stress in rice.